Brachypodium distachyon UNICULME4 and LAXATUM-A are redundantly required for development. Issue 1 (27th September 2021) - Liu, Shengbin; Magne, Kévin; Daniel, Sylviane; Sibout, Richard; Ratet, Pascal
Abstract: In cultivated grasses, tillering, leaf, and inflorescence architecture, as well as abscission ability, are major agronomical traits. In barley ( Hordeum vulgare ), maize ( Zea mays ), rice ( Oryza sativa ), and brachypodium ( Brachypodium distachyon ), NOOT - BOP - COCH - LIKE ( NBCL ) genes are essential regulators of vegetative and reproductive development. Grass species usually possess 2–4 NBCL copies and until now a single study in O. sativa showed that the disruption of all NBCL genes strongly altered O. sativa leaf development. To improve our understanding of the role of NBCL genes in grasses, we extended the study of the two NBCL paralogs BdUNICULME4 ( CUL4 ) and BdLAXATUM - A ( LAXA ) in the nondomesticated grass B. distachyon. For this, we applied reversed genetics and generated original B. distachyon single and double nbcl mutants by clustered regularly interspaced short palindromic repeats – CRISPR associated protein 9 (CRISPR-Cas9) approaches and genetic crossing between nbcl targeting induced local lesions in genomes (TILLING) mutants. Through the study of original single laxa CRISPR–Cas9 null alleles, we validated functions previously proposed for LAXA in tillering, leaf patterning, inflorescence, and flower development and also unveiled roles for these genes in seed yield. Furthermore, the characterization of cul4laxa double mutants revealed essential functions for nbcl genes in B. distachyon development, especially in the regulation of tillering, stem cell elongation and secondary cell wall composition as well as for the transition toward the reproductive phase. Our results also highlight recurrent antagonist interactions between NBCLs occurring in multiple aspects of B. distachyon development. Abstract : UNICULME4 and LAXATUM-A are involved in tillering, tiller elongation, stem cell wall formation, leaf patterning, inflorescence and flower development, and grain yield.